A Static Load Balancing Software for Parallel Applications - Cruz, Adriano Joaquim de Oliveira; Franco, Cláudia Rita de; Vidal, Leonardo Silva (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance Computing, 1999)
This work describes the implementation and benchmarks applied to a load balancing software designed to improve performance of parallel applications running on networks of heterogeneous and non-dedicated workstations. A user level mechanism to gather workload information about each node and the policy to treat this information in order to generate a precise snapshot of the workload of each node of the parallel machine are described throughout this work. An analysis of the main issues concerning workload evaluation is provided, along with a brief explanation on the support offered by current operating systems and ways to overcome their problems. Finally, results and interpretations of comparative tests made between BEC/PVM applications and PVM applications are presented.